PENGARUH KREDIBILITAS INFLUENCER TERHADAP MINAT BELI YANG DIMEDIASI OLEH BRAND AWARENESS LIPSTIK WARDAH DI KOTA BANDUNG - Oktaviani, Denisa; Marliani, Leni Evangalista (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study examines the impact of influencer credibility on consumer purchase intention, where brand awareness of Wardah lipstick serves as a mediating factor in the relationship. The study is situated within the urban market of Bandung City, targeting individuals who are previously unfamiliar with the product.Methods: Employing a quantitative research paradigm, data were obtained through online surveys administered to 90 female participants residing in Bandung. These individuals had not previously purchased Wardah lipstick but had encountered promotional content via social media influencers. The survey instruments underwent rigorous validity and reliability assessments. The next data analysis stage involved applying multiple linear regression using SPSS version 25, while the mediating effect of brand awareness was evaluated through the Sobel test.Results: The findings reveal that the perceived credibility of influencers significantly enhances both brand awareness and the consumers’ inclination to purchase. Moreover, brand awareness positively contributes to purchase intention and serves as a mediating construct linking influencer credibility to consumers’ behavioral intentions.Conclusion and suggestion: These outcomes offer practical implications for businesses seeking to optimize marketing strategies. Collaborations with trustworthy influencers and efforts to bolster brand awareness are recommended to improve the effectiveness of promotional campaigns. Keywords: Influencer Credibility, Brand Awareness, Purchase Intention